THE INFFLUENCE OF CAPITAL STRUCTURE, GOOD CORPORATE GOVERNANCE, DIVIDEND PAYMENT ON EARNINGS QUALITY - Nimita Candraswari; Syarafina Wahyudianti; Afidah Nur Aslamah; Diah Armeliza (Econosains Jurnal Online Ekonomi dan Pendidikan, 2021)
This study aims to examine the effect of capital structure, Good Corporate Governance and dividend payments on earnings quality. Secondary data used on This research focuses on the listed infrastructure, utility and transportation industrieson the Indonesia Stock Exchange (IDX) during the period 2016 – 2019. Samples obtained based on purposive sampling technique with 4 years observation period. This study uses multiple linear regression analysis with a significance level of 5%. The 3 hypotheses are tested by using the Eviews 10 program. Based on the test results multiple linear regression, it can be proved that (a) capital structure has no effect onearnings quality, the amount of debt level cannot affect earnings quality; (b) Good Corporate Governance has a positive effect on earnings quality, the number of committee meetings the audit conducted does not guarantee the good quality of the company's earnings; (c) Dividen payments have a positive effect on earnings quality, companies that pay dividends able to provide a positive market response to earnings quality.